2017
DOI: 10.1002/dneu.22509
|View full text |Cite
|
Sign up to set email alerts
|

Wnt and Shh signals regulate neural stem cell proliferation and differentiation in the optic tectum of adult zebrafish

Abstract: Adult neurogenesis occurs more commonly in teleosts, represented by zebrafish, than in mammals. Zebrafish is therefore considered a suitable model to study adult neurogenesis, for which the regulatory molecular mechanisms remain little known. Our previous study revealed that neuroepithelial‐like neural stem cells (NSCs) are located at the edge of the dorsomedial region. We also showed that Notch signaling inhibits NSC proliferation in this region. In the present study, we reported the expression of Wnt and Shh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…We previously showed that Shh signal‐related genes are expressed in the adult optic tectum and that Shh signaling regulates NE proliferation and differentiation (Shitasako et al, ). In our previous study, it was suggested that Shh signaling up‐regulates NE proliferation and down‐regulates NE differentiation under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that Shh signal‐related genes are expressed in the adult optic tectum and that Shh signaling regulates NE proliferation and differentiation (Shitasako et al, ). In our previous study, it was suggested that Shh signaling up‐regulates NE proliferation and down‐regulates NE differentiation under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that some genes related to Shh signaling, including shha , smo , ptch1 , and ptch2 , are expressed in the adult optic tectum (Shitasako et al, ). Shh ligand binds to transmembrane receptor Patched (Ptch) and Ptch activation leads to the inhibition of Smoothened (Smo) (Lum & Beach, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The function of NE in the regenerative condition and RG in both, physiological and regenerative conditions, are not well known. In the previous studies, we analyzed the function of Wnt signaling on adult neurogenesis in the optic tectum of zebrafish (Shitasako et al, ), and Wnt‐related genes were expressed in the central nervous system of the zebrafish embryo (Clements, Ong, & Traver, ; Duncan, Panahi, Piotrowski, & Dorsky, ; Hashimoto et al, ; Untergasser, Martowicz, Hermann, Töchterle, & Meyer, ). Moreover, other studies also showed that Wnt signaling regulates self‐renewal and differentiation of neural stem cells in the physiological and regenerative conditions in the retina, hypothalamus, and spinal cord (McPherson et al, ; Ramachandran, Zhao, & Goldman, ; Strand et al, ).…”
Section: Introductionmentioning
confidence: 99%